2005
DOI: 10.3748/wjg.v11.i22.3357
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum leptin levels with anthropometric and metabolic parameters and biochemical liver function in Chinese patients with chronic hepatitis C virus infection

Abstract: HCV infection interferes with fat and lipid metabolism in patients with chronic HCV infection and leptin may play a role in hepatosteatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Although leptin regulates feeding behavior, individuals who are obese have high levels of leptin without the expected anorexic responses, due to leptin resistance 8 . Furthermore, because leptin plays a role in host defense mechanisms, the plasma levels of leptin have been reported to increase in infections 30 and in response to proinflammatory stimuli, such as lipopolysaccharide (LPS) and TNF‐α 31 . A recent investigation demonstrated that leptin is able to enhance Prevotella intermedia LPS‐induced TNF‐α production 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Although leptin regulates feeding behavior, individuals who are obese have high levels of leptin without the expected anorexic responses, due to leptin resistance 8 . Furthermore, because leptin plays a role in host defense mechanisms, the plasma levels of leptin have been reported to increase in infections 30 and in response to proinflammatory stimuli, such as lipopolysaccharide (LPS) and TNF‐α 31 . A recent investigation demonstrated that leptin is able to enhance Prevotella intermedia LPS‐induced TNF‐α production 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Serum leptin levels were higher in CHC patients than controls, 53 and associated with the severity of fi brosis. 54 Serum leptin levels correlated with hepatic steatosis in patients infected with hepatitis C virus genotype 3 but not genotype 1.…”
Section: Leptin and Liver Diseasesmentioning
confidence: 96%
“…Pooling data from studies [24,28,35,38] with 1507 participants showed that there was a linear dose-response relationship between AdipoQ levels and HCC risk ( Pnon−linearity = 0.233). We de ned the increment in 1 µg/ml AdipoQ levels as a unit to show the trend more clearly.…”
Section: Dose-response Of Circulating Adipoq Leptin Levels and Hcc Riskmentioning
confidence: 99%